MODEL PENENTUAN HARGA DAN WAKTU PRODUKS1 ORDER PADA PERUSAHAAN MAKE-TO-ORDER JOB-SHOP DENGAN MEMPERTIMBANGKAN ORDER KONTINGENSI - Aisyati, Azizah
Abstract : There are three types of order in a Make-To-Order industry: confirmed order, contingent order and new order. Confirmed order is an order where the consumer has agreed to the estimated cost and delivery time offered by the manufacturer. Contingent order is an order where the manufacturer has offered the estimated cost and delivery time but the consumer has not agreed to the offer. New order is an order received from the consumer and the manufacturer has not yet offered the estimated cost and completion time. <p align="justify" Complexity of cost and delivery time estimation increases when the manufacturer, at the same time, considering contingent orders. An underestimate of cost and delivery time occur if the estimation of new orders does not take into account contingent orders, especially when the contingent order becomes a confirmed order. This results a penalty cost due to delay in delivery time. <p align="justify" The objective of this research is to develop a cost and delivery time estimation model, which takes into account uncertainty of contingent orders. The output of the developed model is the estimated cost and delivery time, which provides maximum revenue for the manufacturer. The model also presents detail activity of each manufacturing resource. <p align="justify" The case study illustrates the application of the model in a real manufacturing company. The application of the model reveals that the price based on estimated cost and delivery time of the model tends to be cheaper and lengthier, rather than the estimates made by the company. The price of the model provides maximum revenue for the manufacturer. The probability of response customer based on estimated cost and delivery time of the model tends to bigger than the probability is estimated by the company.